PENGARUH PENDIDIKAN ISLAM DALAM KELUARGA DAN SEKOLAH TERHADAP SIKAP KEBERAGAMAAN SISWA SDN KURANJI CIREBON - Aisyah Aisyah (Oasis : Jurnal Ilmiah Kajian Islam, 2018)
Religious education in family and school is an important aspect in shaping one's behavior. In general, Islamic studies conducted by instilling religious values, ethics covering perkerti mind, how behavior should be done in everyday life. The problem of this research is "How far is the influence of Islamic religious education in the family and school on the religiousness of SDN Kuranji students of Cirebon city?" This study aims to find out how far the influence of Islamic religious education in family and school on the religiousity of SDN Kuranji students in Cirebon. This research method uses a quantitative approach with research techniques include: study the documentation, literature and questionnaires and data analiisis technique using the formula Pearson Product Momentkajian. The results of this study can be concluded that: the influence of Islamic education in the family against the religiousity of students can be seen from the percentage value with the calculation program (SPSS) 23.0 For Windows obtained t count value of 4.657, while t table with degrees of freedom or degree of freedom (df) = 75 - 2 = 73 at the 0.05 significance level (two-tailed test) of 1.99300. Thus 4.435> 1.99300 so t count> t table. This means that Islamic education in the family has a positive and significant influence on the religiousness of students of SDN Kuranji. The influence of Islamic education in school on the religiousness of the students of SDN Kuranji Cirebon city obtained the value of t arithmetic of 4.213, while t table with degrees of freedom (df) = 75 -2 = 73 at the level of significance 0.05 (double-sided test) of 1.99300. Thus 4.213> 1.99300 so t count> t table. It means that Islamic education has a positive and significant influence on the religiousness of SDN Kuranji students in Cirebon.Â Pendidikan agama dalam keluarga dan sekolahmerupakan aspek penting dalam membentuk perilaku seseorang. Pada umumnya pendidikan agama Islamdilakukan dengan menanamkan nilai-nilai agama, etika yang meliputi budi perkerti, cara tingkah laku yang harus dilakukan dalam kehidupan sehari-hari. Permasalahan dalam penelitian ini adalahâ€œ Seberapa jauh pengaruh pendidikan agama Islam dalam keluarga dan sekolah terhadap keberagamaan siswa SDN Kuranji kota Cirebon ?â€ Penelitian ini bertujuan untuk mengetahuiseberapa jauhpengaruh pendidikan agama Islam dalam keluarga dan sekolah terhadap keberagamaan siswa SDN Kuranji kota Cirebon. Metode penelitian ini menggunakan pendekatan kuantitatif dengan teknik penelitian yang meliputi : studi dokumentasi, studi pustaka dan angket dan teknik analiisis datanya menggunakan rumus Pearson Product Momentkajian. Hasil penelitian ini dapat disimpulkan bahwa pengaruh pendidikan Islamdalam keluarga terhadap keberagamaan siswadapat dilihat dari nilai persentase diperoleh nilai thitungsebesar 4,657, sedangkan ttabeldengan derajat kebebasan atau degree of freedom (df) = 75 - 2 = 73 pada taraf signifikansi 0,05 (uji dua sisi) sebesar 1,99300. Dengan demikian 4,435 > 1,99300 jadi thitung>ttabel. Artinya pendidikan Islamdalam keluarga mempunyaipengaruh positif dan signifikan terhadap keberagamaan siswa SDN Kuranji. Pengaruh pendidikan Islam di sekolah terhadap keberagamaan siswa SDN Kuranji kota Cirebon diperoleh nilai thitungsebesar 4,213, sedangkan ttabeldengan derajat kebebasan atau degree of freedom (df) = 75 -2 = 73 pada taraf signifikansi 0,05 (uji dua sisi) sebesar 1,99300. Dengan demikian 4,213 > 1,99300 jadi thitung>ttabel. Artinya pendidikan Islam mempunyaipengaruh positif dan signifikan terhadap keberagamaan siswa SDN Kuranji kota Cirebon.